Understanding Growth and Poverty : Theory, Policy, and Empirics - Nallari, Raj (World Bank, 2012)
This volume is an introduction to the theories and policies that affect economic growth and poverty. It is a compilation of lecture notes used in face-to-face and e-learning courses presented by the World Bank Institute's (WBI) Poverty Program during 2004-08. The volume is divided into three parts. Part one discusses basic concepts and measurement issues pertaining to poverty, national income, and economic growth. Part two deals with the macroeconomic policies that are critical for economic growth in the short term. It covers government enforced fiscal and exchange-rate policies and the roles of financial institutions, development assistance (or aid), debt relief, and trade policies. Part three covers the structural and sectoral policies that affect longer-term economic growth and poverty reduction. To underscore the impact of good governance and effective service delivery in growth and poverty reduction, separate chapters are devoted to institutional and technological development, education, health, labor, and land. The volume ends with a chapter that summarizes knowledge of growth theory, reviews the process of growth in 13 successful countries, and draws out implications for other developing countries. The authors hope that this chapter may be of help to policy makers in identifying the constraints to economic growth and development that may be unique to each country.